Household Savings and Investment Practices: A Study of the Bhakatpur District, Nepal - Risal, Nischal; Pandey, Dhruba Lal; Shrestha, Ratish (DEPAN, 2024)
The aim of the study is to analyze the saving and investment behavior of households of Bhaktapur District, Nepal. Savings and investments patterns and behavior by the people are also varying from individual to individual and even with the same individual due to motive differences during two periods. The study is quantitative in nature. The study is based on descriptive and analytical research design. The population is the households of Bhaktapur district. Sample size of 200 respondents were selected for the study based on convienience sampling method. SPSS and Excel were used for the analysis of the data. Cronbach’s alpha is calculated for the reliability of the data. The descriptive, correlation and multiple regression analysis are used to analyze the data. The study finds that financial literacy, personal factors and environmental factors have significant positive relationship with saving and investment behavior. Further, the study concluded that personal factors have more impact on saving and investment behavior in the household of Bhaktpur district in Nepal.